Does Bank Efficiency Matter? A Case of Egypt - Hassan Hassan; Ammar Jreisat (International Journal of Economics and Financial Issues, 2016)
This paper offers to measure the efficiency of the Egyptian banks and its determining factors. Using data envelopment analysis in the first stage to find the efficiency level for banks, by comparing the efficiency of large, medium and small banks and the efficiency of foreign and domestic banks through a balanced panel which cover 14 banks operating in Egypt from 1997 to 2013. A detailed analysis per banking group reveals that medium banks are the most efficient ones, followed by foreign banks. In the second stage, potential determinants of technical efficiency are studied using a regression model using method developed by Papke and Wooldridge (1996). The variables LTA, LTD, and NIM are all statistically significant with positive affected on the efficiency level for the Egyptian banks, however, number of branches and NIETA all statistically significant with negatively affected on the efficiency level for the Egyptian banks.